THE INFLUENCE OF MOTIVATION ON BUDGET GOAL COMMITMENT THROUGH THE LEVEL OF PARTICIPATION IN BUDGETING AS A MEDIATOR - Amanda Yunne Erlandian; Enny Prayogo; SeTin SeTin (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2023)
This study aims to investigate and analyze the influence of motivation, consisting of two dimensions, in affecting budget goal commitment through the level of participation in budgeting as a mediator. The two dimensions of motivation referred to are intrinsic motivation and controlled extrinsic motivation. Data were collected through survey-based research by distributing questionnaires to lower-level managers in the garment and textile manufacturing sector in Bandung. To analyze the data and test mediation, this study used a structural equation model (SEM) with the alternative partial least squares (PLS) method. The findings of this study indicate that both intrinsic motivation and controlled extrinsic motivation have a positive effect on the level of participation in budgeting. In addition, the level of participation in budgeting mediates the influence of each motivation dimension on budget goal commitment. Companies can take action to improve budget goal commitment by managing motivation that will impact the level of participation in budgeting.Keywords: budget goal commitment, level of participation in budgeting, motivation